Compensation effects between impurity cations in single crystals of a wide gap semiconductor β-Ga2O3 prepared by the floating zone method. (28th August 2019) - Tomioka, Yasuhide; Ozaki, Yasuko; Inaba, Hideki; Ito, Toshimitsu
Abstract: The resistivity ρ and Hall coefficient R H of a wide gap semiconductor β -Ga2 O3 have been investigated using crystals with various Si-doping that were purified by the zone-melting process. For the crystals with the conduction electron density <∼10 18  cm −3, the n -type conduction is replaced with the impurity conduction at low temperatures, which is manifested as a shoulder (maximum) in the plot of the ρ (– R H ) versus the reciprocal temperature 1/ T, like the compensated n -type germanium. The analysis of the residual impurity cations in a non-doped crystal indicates that besides the 2 ppm of Si the Al, Mg, and Fe are remained in the crystal. Although the Fe and Mg are deep acceptors themselves, analysis of the mobilities indicates that they act like ionized acceptors compensating donors Si. This study demonstrates that the compensation effects between impurity cations are the essential factors for the transport properties in β -Ga2 O3 .